Tinjauan Yuridis Tentang Penyediaan Jasa Catering Dalam Teori Dan Praktek Serta Problematikanya Di Kota Surakarta (Studi Kasus di Beberapa Perusahaan Catering Surakarta) - Nugroho, Irwan Agung; , Septarina Budiwati, SH., M.H; , Darsono, SH., M.H (2015)
This study is included in non-doctrinal law research meaning that law is represented as symbolic meaning of social actors. Research location was in Dahareco Catering, Niekmat Rasa and Sari Catering of Surakarta. Primary data was obtained through interview with the owners of the business and the management. Data analysis technique was conducted using qualitative data analysis method. This study was conducted with the objective to know the implementation of agreement between catering service with the customers and to know the problem and resolution. Based on the results of study, the implementation of agreement in catering service by the business owner and customer was conducted orally and simple in accordance with the the basic requirement of agreement prevails in Civil Acts. Problems was on the term of payment, invalid statement from the customer in order submission, ignored explanation by the customer about errors in presentation, limited document to be used as evidence, unexpected situation in relation with food security and hygiene, miscommunication in menu options. The resolution by the parties was by discusion for good resolution. Keyword: catering service, specific service agreement, breach of contract